Opportunity or Orientation? Who Uses Urban Parks and Why - Lin, Brenda B.; Fuller, Richard A.; Bush, Robert; Gaston, Kevin J.; Shanahan, Danielle F. (PLOS ONE, 2014)
There is growing recognition that interactions with nature provide many desirable human well-being outcomes, yet increasing urbanization is degrading the quality and quantity of nature experiences. Thus, it has become increasingly important to understand how and why urban dwellers interact with nature. Studies of urban green space use have largely focused on the availability and ease of access to green space, suggesting that greater opportunities to experience such space will lead to increased use. However, a growing literature emphasizes the potential for an individual's nature orientation to affect their interaction with green space. Here we measure the importance of both opportunity and orientation factors in explaining urban park use. An urban lifestyle survey was deployed across Brisbane, Australia in November 2012 to assess patterns of green space use. Participants (n = 1479) were asked to provide information on demographics, private yard use, park visitations in the past week, and their orientation toward nature. About 60% of those surveyed had visited a park in the past week, and while this park user population had significantly greater nearby park coverage (within a 250 m radius; p = 0.006), a much stronger determinant of visitation was their higher nature orientation (p<0.00001), suggesting that while both opportunity and orientation are important drivers for park visitation, nature orientation is the primary effect. Park users also spent significantly more time in their yards than non-park users (p<0.00001), suggesting that yard use does not necessarily compensate for lower park use. Park users with stronger nature orientation (i) spent more time in their yard, (ii) traveled further to green spaces, and (iii) made longer visits than park visitors with weaker nature orientation. Overall, our results suggest that measures to increase people's connection to nature could be more important than measures to increase urban green space availability if we want to encourage park visitation.